The Effect of Intelligence Quotient, Emotional Quotient, and Spiritual Quotient on The Ethical Attitude of Accounting Students at Islamic Universities in Pekanbaru (Empirical Study on Riau Islamic University and State Islamic University Sultan Syarif Kasim) - Wahyuningsih, Eny; Suryadi, Nanda (International Journal of Engineering and Technology, 2018)
The research is aimed at: 1) Testing the effect of intellectual intelligence (IQ), emotional intelligence (EQ), and spiritual intelligence (SQ) on ethical attitudes of university accounting students, simultaneously and partially; 2) Testing which variable that has dominant effect. The respondents of the research are accounting students at Islamic University of Pekanbaru, Purposive sampling technique is chosen with criteria respondents have done Auditing I subject. Data was gathered by questionnaires and documentation. Data analysis to test hypothesis was done with multiple linear regression analysis. This research results show that IQ, EQ, and SQ simultaneously had significantly effect on ethical attitudes of university accounting students. But partially, only IQ has significantly and dominantly effects on ethical attitudes of university accounting students.Â Â